Sets of Strong Ground Motion Records Selected Due to Syrian Code Recommendation Which Convey a Wide Range of Civil Buildings Main Periods for All Design Response Spectrums Located in Lattakia - جديد, سراج (Latakia University Journal -Engineering Sciences Series, 2021)
Selecting seismic records in Global Standards until now is based on matching design response spectrum, where records should have seismological characteristics similar to the expected earthquake for the considered site (magnitude, distance, fault mechanism and soil conditions). Then it is necessary to scale these records to match the intensity of the earthquake expected for the site. Generally, scaling can be made by ground motions uniform scaling in time domain to best match (in average) the target spectrum within a period range of interest. Design ground motions are typically prescribed by smooth response spectra. But it is preferred to use a set of time histories that are representative of the design target spectrum in an ensemble average. That’s Due to the increase of available strong ground motion database and improving computing power. In this study, basic methodologies for selecting and scaling strong ground motion time histories are summarized and utilized to obtain 40 sets of real seismic records that are sufficient to Tartous city’s needs. These sits are conveying a wide range of classic buildings periods, and all soil types Sa, Sb, Sc, Sd and Se, which means the city’s five design spectra. Thus Syrian engineer can safely use these records in linear and nonlinear analyses recommended for design and research purposes.